Hyperimmune globulins and same‐day thrombotic adverse events as recorded in a large healthcare database during 2008–2011. Issue 12 (12th September 2013) - Menis, Mikhail; Sridhar, Gayathri; Selvam, Nandini; Ovanesov, Mikhail V.; Divan, Hozefa A.; Liang, Yideng; Scott, Dorothy; Golding, Basil; Forshee, Richard; Ball, Robert; Anderson, Steven A.; Izurieta, Hector S.
Abstract : Thrombotic events (TEs) are rare serious complications following administration of hyperimmune globulin (HIG) products. Our retrospective claims‐based study assessed occurrence of same‐day TEs following administration of HIGs during 2008–2011 and examined potential risk factors using HealthCore's Integrated Research Database (HIRD SM ) and laboratory testing of products' procoagulant Factor XIa activity by U.S. Food and Drug Administration. Multivariable regression was used to estimate same‐day TE risk for different products. Of 101, 956 individuals exposed to 23 different HIG product groups, 86 (0.84 per 1, 000 persons) had a TE diagnosis code (DC) recorded on the same day as HIG administration. Unadjusted same‐day TE DC rates (per 1, 000 persons) ranged from 0.4 to 148.9 for different products. GamaSTAN S/D IG >10 cc had statistically significantly higher same‐day TE DC risk compared to Tetanus IG (OR = 57.57; 95% CI = 19.72–168.10). Increased TE risk was also observed with older age (≥45 years), prior thrombotic events, and hypercoagulable state(s). Laboratory investigation identified elevated Factor XIa activity for GamaSTAN S/D, HepaGam B, HyperHep B S/D, WinRho SDF, HyperRHO S/D full dose, and HyperTET S/D. Our study, for the first time, identified increase in the same‐day TE DC risk with GamaSTAN S/D IG >10 cc and suggests potentially elevated TE risk with other HIGs. Am. J. Hematol. 88:1035–1040, 2013. © 2013 Wiley Periodicals, Inc.